Analisis Penerapan Sistem Manajemen Mutu Berdasarkan ISO 9001:2015 Pada RS Islam Malahayati - maulidia, Indah; Aslami, Nuri; Imsar, Imsar (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the implementation of the ISO 9001:2015 Quality Management System at Malahayati Islamic Hospital using a qualitative descriptive approach. Data were collected through interviews with hospital stakeholders. The hospital applies ISO principles such as customer focus, process approach, and continuous improvement through training, documentation, audits, and reviews. While efficiency has improved, challenges remain, including limited human resources and inter-unit integration. Patient satisfaction and staff compliance are generally positive. The study highlights the role of ISO in enhancing hospital performance and integrates Islamic ethical values, offering a novel perspective on strengthening quality culture in Islamic healthcare institutions.